2021
DOI: 10.1103/physrevmaterials.5.094407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic anisotropy relaxation on laser-induced magnetization precession in thin galfenol films

Abstract: The rate and pathways of relaxation of a magnetic medium to its equilibrium following excitation with intense and short laser pulses are the key ingredients of ultrafast optical control of spins. Here we study experimentally the evolution of the magnetization and magnetic anisotropy of thin films of a ferromagnetic metal galfenol (Fe0.81Ga0.19) resulting from excitation with a femtosecond laser pulse. From the temporal evolution of the hysteresis loops we deduce that the magnetization MS and magnetic anisotrop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…It was previously suggested that such a behavior of ω FM ( T ( t )) could be used to study the exact evolution of magnetic anisotropy after ultrafast laser excitation. [ 51 ]…”
Section: Discussionmentioning
confidence: 99%
“…It was previously suggested that such a behavior of ω FM ( T ( t )) could be used to study the exact evolution of magnetic anisotropy after ultrafast laser excitation. [ 51 ]…”
Section: Discussionmentioning
confidence: 99%
“…34 The single film has a thickness comparable to the total thickness of the layered structure, and thus it is used as a reference to determine the MSW dispersion in the case of a single film. We choose galfenol-based structures because they exhibit low Gilbert damping, 35 high values of magnetization precession lifetime 36,37 and long MSW propagation length, 38 which makes galfenol a prospective material for magnonic applications. According to ferromagnetic resonance measurements, the saturation magnetization of the ferromagnetic layers is estimated as μ 0 M s = 1.7 T at layer thicknesses of 7 and 20 nm.…”
Section: Sample and Methodsmentioning
confidence: 99%
“…The observed spectral evolution is associated with different MSSW dispersion relations inside and outside the pump-heated area. Indeed, effective anisotropy fields are partially suppressed by an abrupt decrease of the anisotropy parameters and magnetization inside the excitation area 32 . This leads to a shift of the MSSW dispersion inside the pump area to the higher or lower frequency range depending on the orientation of H because of the different manner in which the anisotropy field enters the total effective field: i.e.…”
mentioning
confidence: 99%
“…It is worth mentioning that the spectral asymmetry of the precession inside the pump spot is attributed to another origin. Particularly, the precession occurs in the abruptly heated trap for MSSWs 35,36 with the temperature recovery on the order of several hundred picoseconds 32,36 . The corresponding evolution of the magnetic parameters results in a gradual recovery of the pump-induced up-(down-)shift of the frequency back to its equilibrium value, giving rise to longer lifetimes and higher FFT amplitudes of the bottom (top) part of the This is the author's peer reviewed, accepted manuscript.…”
mentioning
confidence: 99%